Mitogenomes Provide Insights Into the Evolution of Thoracotremata (Brachyura: Eubrachyura) - Sun, Shao’e; Jiang, Wei; Yuan, Ziming; Sha, Zhongli (Frontiers in Marine Science, 2022)
Thoracotremata is a group of Brachyura, with 1,248 extant species. To date, parts of the thoracotreme phylogeny are not yet resolved and require further investigation. In this study, 12 new mitogenomes from the four thoracotreme superfamilies were sequenced. They contain a standard set of 37 genes, and vary in size from 15,422 (Hapalocarcinus marsupialis Stimpson, 1858 sensu lato) to 16,490 bp [Arcotheres sinensis (Shen, 1932)]. Combined with 58 thoracotreme mitochondrial genomes (mitogenomes) from GenBank, we described the evolution of gene rearrangement and the internal phylogenetic relationships of Thoracotremata, and evaluated the phylogenetic position of Cryptochiroidea and Pinnotheroidea. Nine distinct patterns of mitochondrial gene order (MGO) among thoracotreme mitogenomes are identified, with four MGOs newly found in Thoracotremata. All other gene orders are the result of transformational pathways originating from brachyuran gene order (BraGO). The different gene orders have variable levels of gene rearrangements, which involve both tRNAs and protein-coding genes. No link between variable gene arrangements (breakpoint distances) and nucleotide substitution rates (branch lengths) is found in thoracotreme crabs. The symbiotic groups, the cryptochiroid and pinnotheroid crabs, display variable MGOs (CryGO, Pin1GO, and Pin2GO), providing evidence for possible correlations of rearranged MGOs to the adaptations to specialized lifestyles. In our phylogenetic analyses, Cryptochiridae (Cryptochiroidea) show close relationship with an Ocypodoidea lineage (Camptandriidae/Xenophthalmidae/Dotillidae). Pinnotheridae (Pinnotheroidea) form the basal monophyletic clade.